Activation of mast cells mediates inflammatory response in psoriasis: Potential new therapeutic approach with IL‐37. Issue 4 (3rd May 2019) - Conti, Pio; Gallenga, Carla Enrica; Ronconi, Gianpaolo; Caraffa, Alessandro; Kritas, Spyros K.
Abstract: Psoriasis (PS) is an autoimmune disorder characterized by chronic inflammatory skin immune‐mediated disease which occurs in 2–4% of the worldwide population. PS is associated with an increased risk of cardiovascular disease and depression, and 30% of PS patients are affected with psoriatic arthritis. PS presents excessive keratinocyte proliferation, abnormal differentiation, and elevated mast cell (MC) number. In PS, there are enhanced type I interferon (IFN), angiogenesis, and over‐expression of several proinflammatory cytokines, such as tumor necrosis factor and interleukin (IL)‐1 family members generated by several immune cells including MCs. MCs are hematopoietic cells that reside in vascularized tissues, which, upon appropriate activation, release proinflammatory cytokines, an effect worsened by acute stress and PS. In recent years, IL‐37 emerged as an anti‐inflammatory cytokine which binds to alpha chain of the IL‐18 receptor alpha (IL‐18Rα) and downregulates MyD88. This effect leads to the inhibition of nuclear factor‐κB (NF‐κB) and mitogen activation protein kinase, with the suppression of inflammatory response. These observations candidate IL‐37 as a potential new therapeutic cytokine for inflammatory disorders including PS.